Regulation of AGR2 expression via 3'UTR shortening - Matoulkova, Eva; Sommerová, Lucia; Pastorek, Michal; Vojtesek, Borivoj; Hrstka, Roman (Experimental cell research, 2017)
One recently discussed general mechanism affecting gene expression is 3'-untranslated region (3'UTR) length. Events such as shortening, translocation or loss of 3'UTRs are observed within oncogenes and are proposed to associate with increased expression. Thus, increased efforts are being made to understand constitutive and differential transcript 3'end formation. Investigation of AGR2 mRNA revealed a direct impact of its 3'UTR length on AGR2 expression. In silico analyses identified several regulatory sequences within the distal part of AGR2 mRNA that may regulate 3'UTR length and associated protein levels. Short 3'UTRs were observed in a panel of AGR2-positive cancer cell lines and in human breast cancer specimens, in which more extensive 3'UTR shortening correlated with increased AGR2 protein levels. AGR2 is an important member of PI3K/AKT signalling pathway, which along with the proposed involvement of mTOR in the regulation of alternative polyadenylation, prompted us to study the role of mTOR in relation to AGR2 mRNA 3'UTR shortening. A direct impact of mTOR signalling on AGR2 3'UTR shortening associated with increased protein synthesis was found, which led to the identification of a novel molecular mechanism involved in upregulation of AGR2 levels in mTOR-activated cells via modulating the 3'UTR length of AGR2 mRNA.
Keywords: buňky A549; Regulatory Sequences, Ribonucleic Acid; HEK293 buňky; Up-Regulation; Signal Transduction; nádory prsu; HEK293 Cells; HCT116 Cells; Cloning, Molecular; Humans; nádorové buněčné linie; Multiprotein Complexes; Proteins; messenger RNA; Breast Neoplasms; regulace genové exprese; signální transdukce; Gene Expression Regulation; Polyadenylation; MFC-7 buňky; proteiny; MCF-7 Cells; HCT116 buňky; upregulace; multiproteinové komplexy; TOR serin-threoninkinasy; ženské pohlaví; TOR Serine-Threonine Kinases; 3' nepřekládaná oblast; polyadenylace; Protein Biosynthesis; lidé; proteosyntéza; RNA, Messenger; klonování DNA; A549 Cells; regulační sekvence ribonukleových kyselin; 3' Untranslated Regions; Cell Line, Tumor; Female